Prospects for sustainable intensification of soybean production in sub-Saharan Africa - Debnath, Deepayan; Babu, Suresh Chandra (African Association of Agricultural Economists, 2020)
There is a significant soybean yield gap in sub-Saharan African (SSA) countries. Sustainable intensification of the agricultural sector to reduce such a yield gap is important. Increasing soybean productivity can meet the growing demand for food and feed when complemented with higher soy meal demand by the local livestock industry. This study performs an ex-ante economic analysis to determine the effect of higher soybean production on trade and land use within SSA countries. We find that increasing soybean yield by 50% can increase the total returns from soybean production by 186 million LC (local currency) in Ethiopia and 36 billion LC in Nigeria. We show that soybean yield growth alone is enough to boost soy oil production, as the crushing of the beans produces 18% oil and 79% meal. While increasing productivity may lead to freeing land to produce high-valued cash crops, investors will be reluctant to invest in the crushing facilities in the absence of soy meal demand by the livestock industry. Therefore, policymakers need to establish collaboration between development organisations, private companies, farmers and researchers to achieve this transformation and thereby raise agricultural productivity.